Predictive Value of Cetuximab-Induced Skin Toxicity in Recurrent or Metastatic Squamous Cell Carcinoma of the Head and NECK - Uozumi, Shinya; Enokida, Tomohiro; Suzuki, Shinya; Nishizawa, Aya; Kamata, Hayato; Okano, Tomoka; Fujisawa, Takao; Ueda, Yuri; Okano, Susumu; Tahara, Makoto; Yamaguchi, Masakazu (Frontiers in Oncology, 2018)
Background Skin toxicity is a common adverse event during cetuximab (Cmab) treatment. However, few reports have investigated the correlation between skin toxicity and the efficacy of Cmab in patients with recurrent or metastatic squamous cell carcinoma of the head and neck (R/M SCCHN). Methods We retrospectively reviewed 112 R/M SCCHN patients who received palliative chemotherapy with Cmab. Main eligibility criteria included primary disease in the oral cavity, hypopharynx, nasopharynx, oropharynx, or larynx; no prior history of EGFR-directed therapy; receipt of Cmab plus chemotherapy as first-line therapy for recurrent or metastatic disease; and follow-up for more than 90 days. We analyzed the time to first occurrence and time of maximum grade skin toxicity, and its predictive value with regard to treatment efficacy. Results After a median follow-up of 393 days (range 109–1501 days), 105 (94%) and 20 (18%) patients had skin toxicity of any grade and grade 3 or higher, respectively. Among them, 8 patients with grade 3 or higher acneiform rash, skin rash or paronychia within 90 days after treatment initiation (“early skin toxicity”) had improved progression-free survival (PFS) (log-rank test, P = 0.045; 2-year PFS, 25.0% vs. 2.9%) and overall survival (OS) (log-rank test, P = 0.023, 2-year OS, 50.0% vs. 14.4%) compared with those with < grade 3 toxicity. A greater proportion of patients with early skin toxicity than patients without this toxicity could proceed with Cmab maintenance (88% vs. 44%, P = 0.021). Multivariate analysis identified early skin toxicity as an independent predictor of better PFS (hazard ratio [HR] = 0.363, 95% confidence interval [CI] 0.142–13924, P = 0.034) and OS (HR = 0.187, 95% CI: 0.045–0.781, P = 0.022). Conclusion Grade 3 or higher Cmab-induced skin toxicity within 90 days was associated with better survival in R/M SCCHN. Effective rash management therefore seems necessary to realize the benefit of Cmab treatment.